Who’s at the table? Disaster committee composition and policy pathways after Hurricane Sandy - Fraser, Timothy; Hewitt, Lucy; Chen, Jessica; Cherkerzian, Matthew; Rago, Vincent; Aldrich, Daniel P. (Journal of environmental management, 2025)
While scholars argue that resident participation in disaster recovery policymaking matters, few research teams have captured the composition of disaster recovery committees after shock. This study examines how the composition of disaster recovery committees influenced recovery plans following Hurricane Sandy in 2012. Analyzing all 47 NY Rising Community Reconstruction Program committees, we catalogued professional and demographic traits of members and conducted quantitative text analysis on their recovery plans. Findings indicate that greater community participation was negatively associated with government and expert involvement, reflecting similar trends in past disasters. Committees with more community participation tended to incorporate more soft policy language, focusing on community development rather than hard infrastructural solutions. Contrary to expectations, committees with more business representatives particularly emphasized soft over hard policy themes. These results highlight how interest group representation shapes disaster recovery planning, underscoring the need for inclusive participation to ensure socially conscious recovery efforts. Our study provides empirical insights for policymakers aiming to design more representative and responsive disaster governance. •Disaster recovery committee composition analyzed across 47 NY Rising groups.•Greater community participation correlated with lower government involvement.•Committees with more community participation emphasized soft policy.•Business representatives unexpectedly prioritized soft policy themes.•Findings inform inclusive disaster recovery and governance strategies.